PEMBUATAN MEDIA PEMBELAJARAN BELAJAR PARTS OF SPEECH BERBASIS ANDROID - Hafni Hafsah; Willyansah Willyansah (Universitas Nusa Cendana, 2021)
One of the uses of technology in education that supports the teaching and learning process is learning media through an Android-based smartphone. When it relates to learning English, smartphones can function as a tool to attract students' interest and related parties in learning grammar in English, especially parts of speech. The selection of parts of speech as content in this study is due to student’s understanding of the form of words, the meaning of words, and proper and correct usage. Therefore, to improve students' competence in English, it is necessary to build an Android-based application that is more attractive, practical, and full of knowledge in learning parts of speech as one of the strategies for learning English. This study aims to build an Android-based application that contains video, learning materials, exercises, and interactive tests made by a teacher. The method used for this research is System Development Life Cycle (SDLC); it refers to the model and process used to develop a software system and describes the process; where the developer accepts the move from problem to solution. The collection of data was done through an interview with related school parties and through observation. It was processed and analyzed, where the need of the users, in this case, are administrators, teachers, and students, are fulfilled. This application contains video, lesson material, exercise, and tests, where teachers, later on, are expected to be able to create the content on their own. and the students can learn anywhere. The lesson materials on the application can be viewed in 2 (two) ways; they are online and offline, intended to bring access to all students toward lesson materials by using a smartphone.